Hungary : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
The Hungarian government implemented significant restraint and reforms in the mid-1990s, but substantial challenges remain in the medium term. Medium-term fiscal framework will assist in evaluating the preferred approach to managing this range of expenditure pressures and structural reform issues. The paper presents scenarios illustrating the tensions in fiscal policy, and the potential role for medium-term expenditure restraint to achieve fiscal objectives while facilitating growth. The statistical data on the economic indices of Hungary are also presented in the paper.